PERINATAL AND HEREDITARY RISK FACTORS OF HEART RATE AND CONDUCTION DISORDERS IN CHILDREN WITH GASTROESOPHAGEAL REFLUX - Oksana M. Herasymova; Volodymyr M. Savvo (Східноукраїнський медичний журнал, 2021)
Objective: to improve the early diagnosis of cardiac arrhythmias and conduction disorders in children with gastroesophageal reflux by evaluating hereditary and perinatal risk factors for this pathology.